PERSPECTIVES OF DEVELOPING DIGITAL EDUCATION IN MILITARY INSTITUTIONS - Spridzans, Martins (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Digital education and education transformation perspectives have particularly become the topics of interest and research during Covid-19 pandemic in all law enforcement institutions. Experience gained by overcoming weaknesses in e-learning and best practices identified need to be summarised and shared in order to strengthen existing border guards e-learning systems as well as timely prepare infrastructure and trainers for unexpected challenges and future education trends. The article outlines research results on the analysis of the current trends in digital learning in context of e-learning in the State Border Guard as a part of military education system in Latvia. Article includes research of main problems, risks and concerns regarding digital education in general as well as well as potential opportunities and recommendations for further development of e-learning for the Border Guard and the military.  Existing problematic areas have been identified by historic research method, particularly from Covid-19 pandemic distance learning experience. Future perspectives in developing border guard’s digital education capacity and potential have been defined based on analysis of scientific literature, empirical observations based on experience lecturing within military education environment.